2010
DOI: 10.1158/0008-5472.can-09-2758
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Activator of NF-κB Ligand Enhances Breast Cancer–Induced Osteolytic Lesions through Upregulation of Extracellular Matrix Metalloproteinase Inducer/CD147

Abstract: Breast cancer shows a strong predilection to metastasize to bone. Cell surface glycoprotein extracellular matrix metalloproteinase inducer (EMMPRIN)/CD147 induces metalloproteinases (MMP) and vascular endothelial growth factor (VEGF), which may support osteoclastic activity and increased incidence of breast cancer bone metastases. In support of this hypothesis, we observed that MDA-MB-231 human breast tumor cells engineered to overexpress EMMPRIN strongly induced osteolytic lesions in immunodeficient mice, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 38 publications
2
40
0
8
Order By: Relevance
“…Endo180 and CD147 have both been correlated with low levels of E-cadherin in tumor tissue, and both are under the transcriptional regulation of the core EMT trigger TGFb (7,8,19,20). In an aligned study, we have demonstrated that the stiff microenvironment associated with advanced glycation endproduct accumulation and collagen crosslinking of the basement membrane in the prostate gland is sufficient to activate an EMTlike phenotype in PEC acini by forcing the relocalization of Endo180 into endosomes and initiating an Endo180-dependent contractile signaling cascade that promotes cell invasion (21).…”
Section: Discussionmentioning
confidence: 99%
“…Endo180 and CD147 have both been correlated with low levels of E-cadherin in tumor tissue, and both are under the transcriptional regulation of the core EMT trigger TGFb (7,8,19,20). In an aligned study, we have demonstrated that the stiff microenvironment associated with advanced glycation endproduct accumulation and collagen crosslinking of the basement membrane in the prostate gland is sufficient to activate an EMTlike phenotype in PEC acini by forcing the relocalization of Endo180 into endosomes and initiating an Endo180-dependent contractile signaling cascade that promotes cell invasion (21).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of regulation of endogenous CD147 expression are not well established, although several growth factors and cytokines have been shown to increase CD147 levels in a variety of contexts (Hagemann et al, 2005;Menashi et al, 2003;Reddy et al, 2010;Rucci et al, 2010). Previous studies have shown that Src is a crucial regulator of invadopodia formation (Murphy and Courtneidge, 2011), and a recent study showed that the Src family kinase, Fyn kinase, induces emmprin expression (Ramos and Dang, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Expression analyses and treatment of cells in vitro with RANKL have shown functional RANK protein expression on the surface of prostate, breast, osteosarcoma, melanoma, and lung cancer cell lines. In most studies, RANKL does not seem to increase proliferation of RANK-expressing tumor cells (46,47), although increased cell number and protection against DNA damage-induced cell death, activated by either chemotherapy or g-irradiation, have been observed in certain cell lines (43). In addition, RANKL will affect a variety of other tumor cell behaviors potentially relevant to tumor progression and metastasis, including increased tumor cell growth in semisolid media, loss of apical-basal polarity, and stimulated migration and invasion (38,43,45,46,48,49).…”
Section: A Direct Role Of the Rankl Pathway In Distant Metastasesmentioning
confidence: 99%
“…In addition, RANKL will affect a variety of other tumor cell behaviors potentially relevant to tumor progression and metastasis, including increased tumor cell growth in semisolid media, loss of apical-basal polarity, and stimulated migration and invasion (38,43,45,46,48,49). RANKL treatment has been documented to induce a variety of factors potentially involved in migration, angiogenesis, and invasion, including MMP1, MMP9, the matrix metalloproteinase inducer EMMPRIN/CD47, ICAM-1, IL-6, IL-8, and VEGF (47), and it can decrease expression of the metastasis suppressor serpin 5b/maspin (50).…”
Section: A Direct Role Of the Rankl Pathway In Distant Metastasesmentioning
confidence: 99%